Selective elimination of immunosuppressive T cells in patients with multiple myeloma - Awwad, Mohamed; Mahmoud, Abdelrahman; Bruns, Heiko; Echchannaoui, Hakim; Kriegsmann, Katharina; Lutz, Raphael; Raab, Marc-Steffen; Bertsch, Uta; Munder, Markus; Jauch, Anna; Weisel, Katja; Maier, Bettina; et al. (Leukemia, 2021)
Elimination of suppressive T cells may enable and enhance cancer immunotherapy. Here, we demonstrate that the cell membrane protein SLAMF7 was highly expressed on immunosuppressive CD8+CD28-CD57+ Tregs in multiple myeloma (MM). SLAMF7 expression associated with T cell exhaustion surface markers and exhaustion-related transcription factor signatures. T cells from patients with a high frequency of SLAMF7+CD8+ T cells exhibited decreased immunoreactivity towards the MART-1aa26-35*A27L antigen. A monoclonal anti-SLAMF7 antibody (elotuzumab) specifically depleted SLAMF7+CD8+ T cells in vitro and in vivo via macrophage-mediated antibody-dependent cellular phagocytosis (ADCP). Anti-SLAMF7 treatment of MM patients depleted suppressive T cells in peripheral blood. These data highlight SLAMF7 as a marker for suppressive CD8+ Treg and suggest that anti-SLAMF7 antibodies can be used to boost anti-tumoral immune responses in cancer patients.